1997 год. Весенняя сессия, 25 апреля - 4 июня - Теплова М. О. (1999)
Экземпляры: КХ (20010112) / Инвентарный номер: 1036725 / Цена: 15.00 / Сис.шифр: 67.400 / Авт.знак: Г72 / ГРНТИ: 10 / ББК: 67.400.621